Self-talk (positive and negative) and its relationship to Athletic Fears withen the advanced players of Mosul City Center club’s - هشام محمد علي السيدية أ.د ثامر محمود ذنون (الرياضة المعاصرة)
The aim of the current research is to try to uncover the effect of positive and negative psychological skill for self-talk among the advanced club players of Mosul city center, and the researchers seek that the results of this study be of help to the players and those in charge of the training process in order to develop positive psychological skills for self-talk, as well as to reveal the relationship between Self-talk and mathematical concerns of athletes. The researchers used the descriptive method in the survey method, due to its suitability to the nature of the research. The research sample included the advanced players in the Mosul city center clubs who were deliberately selected in order to achieve the objectives of the research. Their number reached (130) players distributed among the sports clubs, and they represent 30% of the research community.